2001
DOI: 10.1007/s289-001-8194-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition in swollen gels

Abstract: The swelling and mechanical behaviour of ionized networks of N-isopropylacrylamide with an ionic comonomer, (2-acrylamidoethyl)trimethylammonium chloride (mole fractions x S = 0-0.1), in the presence of a crosslinker, N,N'-methylenebisacrylamide, was investigated in water as a function of temperature and in aqueous NaCl solutions (c NaCl = 10 -5 − 1 M) at 23 °C. On heating, a continuous decrease in the swelling degree in water, Q w , was observed; increasing x S shifts the volume transition temperature, T tr ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Similar results were obtained for PIPAAm gels. 24 As expected, the swelling degree in water at 23 C, Q w , increases with ionic comonomer concentration, x S (Table 1). As we know all network structure parameters (u d ,r,v 1 ), and if we further assume that the degree of ionization i ¼ x S , we can use eqn.…”
Section: Comparison Of the Theory Of Swelling Equilibria For Polyelec...supporting
confidence: 74%
See 3 more Smart Citations
“…Similar results were obtained for PIPAAm gels. 24 As expected, the swelling degree in water at 23 C, Q w , increases with ionic comonomer concentration, x S (Table 1). As we know all network structure parameters (u d ,r,v 1 ), and if we further assume that the degree of ionization i ¼ x S , we can use eqn.…”
Section: Comparison Of the Theory Of Swelling Equilibria For Polyelec...supporting
confidence: 74%
“…A similar effect was observed earlier for charged PIPAAm hydrogels. 24 In Fig. 3(c) the dependence of log G r on log Q s for samples measured in aqueous NaCl solutions is also shown.…”
Section: Swelling and Mechanical Behavior In Aqueous Nacl Solutionsmentioning
confidence: 97%
See 2 more Smart Citations
“…[23][24][25][26] Elasticity measurements of charged poly͑N-isopropylmethacrylamide͒ gels showed that charges induce hysteresis in swelling, while neutron scattering studies of poly͑N-alkylacrylamide͒ gels have showed coiled and globular conformations below and above the lower critical solution temperature ͑LCST͒. [23][24][25][26] Elasticity measurements of charged poly͑N-isopropylmethacrylamide͒ gels showed that charges induce hysteresis in swelling, while neutron scattering studies of poly͑N-alkylacrylamide͒ gels have showed coiled and globular conformations below and above the lower critical solution temperature ͑LCST͒.…”
Section: Introductionmentioning
confidence: 99%